2016
DOI: 10.1111/jbg.12186
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association study of immune traits in chicken F2 resource population

Abstract: Immune traits play pivotal roles in animal immune capacity development and disease resistance. Single nucleotide polymorphisms (SNPs) are common forms of genetic variations among individuals, which are thought to account for the majority of inherited phenotypic variations. In this study, we performed genomewide association, using the Illumina 60K SNP BeadChip studies to detect molecular markers and candidate genes associated with immune traits in an F2 population. Sixteen immune traits were measured. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Thus, we also compared our gene lists (Tables 1, 2 and 3) with gene entries in the ChickenQTLdb (https://www.animalgenome.org/cgi-bin/QTLdb/GG/ index) related to QTL for production traits and only identified a single gene. LPP, noteworthy one of the genes found in common between FPD and pEFP (Table 3), has been reported to be linked to shank length and diameter [21] as well as Bursa of Fabricius weight [22]. The latter finding might correspond the observation of feather pecking being related to the immune system, but this is speculative and needs to be further investigated.…”
Section: Variance Explained By Markers Gwas and Variant Effect Predimentioning
confidence: 98%
“…Thus, we also compared our gene lists (Tables 1, 2 and 3) with gene entries in the ChickenQTLdb (https://www.animalgenome.org/cgi-bin/QTLdb/GG/ index) related to QTL for production traits and only identified a single gene. LPP, noteworthy one of the genes found in common between FPD and pEFP (Table 3), has been reported to be linked to shank length and diameter [21] as well as Bursa of Fabricius weight [22]. The latter finding might correspond the observation of feather pecking being related to the immune system, but this is speculative and needs to be further investigated.…”
Section: Variance Explained By Markers Gwas and Variant Effect Predimentioning
confidence: 98%
“…The remaining 7 singleton 163 proteins were TNFSF12-TNFSF13, AC073610.3 (Novel Protein), C1RL, FBLN2, OLFML3, SBSN 164 and C4orf54. They may play an important role in avian influenza infection, for instance, protein 165 AC073610.3 acts as GTP binding and obsolete signal transducer activity, the most related GGA2 166 protein associated with avian influenza antibody titers [18]. There were still 51 proteins that were not 167 annotated by the String system.…”
Section: Differential Expression Profiles Of Comparison H7n9 Infectedmentioning
confidence: 99%
“…Currently, a large amount of candidate genes were identified as causal markers associated with growth performance, meat quality, carcass traits, feather colors, and disease resistance ability in the Chinese indigenous chicken population ( Luo et al, 2014 ; Zhang et al, 2015 ; Mao et al, 2019 ; Guo et al, 2020 ; Zhang et al, 2020 ). For example, GWAS in an F 2 resource population was conducted to identify two novel candidate genes related to three single-nucleotide polymorphisms (SNPs) associated with avian influenza antibody titers ( Sun et al, 2016 ). Another study reported that 21 candidate genes were proved to be associated with chicken bone growth based on GWAS in an F 2 crossbred experimental population ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%